Coronal mode ultrasound guided hemodialysis cannulation: A pilot randomized comparison with standard cannulation technique. Issue 1 (9th January 2017) - Kumbar, Lalathaksha; Soi, Vivek; Adams, Elizabeth; Brown Deacon, Cheryl; Zidan, Mohamed; Yee, Jerry
Abstract: Background: Infiltrations from cannulation result in significant morbidity including loss of hemodialysis (HD) vascular access (VA). Cannulation is dependent on personnel skill and VA characteristics. Surface marking of VA lacks real‐time information and traditional ultrasound (US) devices are large, expensive, requiring skilled operators. Sonic Window© (Analogic Ultrasound, Peabody, MA, USA) is a coronal mode ultrasound device (CMUD) approved for VA cannulation. Methods: Single center randomized, prospective pilot study comparing handheld US‐guided cannulation of new arteriovenous fistula (AVF) to standard cannulation practices. Patients with end stage renal disease (ESRD) on in‐center HD who had a new AVF cleared for cannulation and dialysis were enrolled. Patients with new AVF received either standard cannulation (control group) or image guidance using CMUD (study group) for 3 weeks. Ultrasound characteristics of VA, cannulation practices and complications end points were obtained. Results: An infiltration rate of 9.7% was noted during the study. Slightly lower odds ratio (OR) of infiltration was observed in the study group (OR 0.94, 95% CI: 0.26–3.41, P value = 0.93). Study group yielded longer time for assessment (101.8 ± 80.2 vs. 22.3 ± 22.5 seconds, P = < 0.001), increased cannulation time (41.1 ± 70.6 vs. 25.0 ± 27.9 seconds, P = 0.04), and increased patient satisfaction (94.6% vs. 82%, P = 0.04) compared to control group. Number of cannulation attempts, needle size, arterial or venous needle insertion, and tourniquet usage between groups were not statistically different. Conclusion: Handheld ultrasound is a safe and useful aid in cannulation of dialysis access.